Improvement of the state policy on implementation of the "green" economy in Ukraine - Polishchuk Y.A. (Theory and Practice of Public Administration, 2019)
The concept of «green economy» adopted by the world community is designed to ensure the harmonization of the three components of sustainable development – economic, social and environmental. «Green Economy» is not just a possibility but a compulsory way of development for all countries and nations if they want to ensure a secure future for their citizens. The transition to a green economy has a long and difficult path, but today a number of advanced economies and developing countries (USA, Germany, Japan, Denmark, Republic of Korea, Mexico, China, the Republic of Namibia, etc.) demonstrate leadership by adopting «green» economic strategies.In this paper actualized problems in the transition of society to priority innovation areas «green» economy. It has been noted comparative characteristic: «green» economy, «green» growth and sustainable development. Analysis of strategic priorities for the formation of new «green» areas of economics and environmental management transformation of existing industries. Pointed technically feasible potential of renewable energy as a practical mechanism to ensure economic security in terms of threats to resource depletion. The priority public policy based on the introduction of innovative environmentally sound technologies that will ensure the sustainable development of society in a strategic perspective .innovative environmentally sound technologies that will ensure the sustainable development of society in a strategic perspective.The author analyzes the concept as an important component of socio-economic development of the state, shows its importance to the national economy. Strategic priorities involvement of the Ukrainian regions’ «green» economics potential as the basis for the formation of «growth points» and «economic development areas» at the local and regional level has been reasonable.In paper it is proved that the development of « green» economics contributes to solute several system problems of the regions in Ukraine: reduces energy production, stimulates the transition to alternative energy, which creates jobs and improves the quality of life in the regions.